2014
DOI: 10.1007/978-1-4614-3209-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Infiltration of Monocyte Derived Cells and Complement Misregulation in Mice with AMD-Like Pathology

Abstract: We have characterized a naturally-occurring mutation in mice that causes slow, progressive photoreceptor degeneration, white fundus flecks, and late-onset RPE atrophy. These animals predictably lose visual function as photoreceptors degenerate. Genetic studies identified a deletion in the 5′ coding sequence of Mfrp, designated Mfrp174delG, which essentially results in a complete knockout at the protein level. We have shown in Mfrp174delG mice that these white fundus flecks are due to the presence of F4/80+ inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In IR mode, retinal lesions were visualized as a result of employing small adjustments to the SLO focus which served to accentuate lesion contrast against the RPE and choroidal background. Retinal lesions were found to be retinal infoldings, invaginations and/or deviations as previously reported by histology in other mouse models of retinal degeneration (Akhmedov et al, 2000; Hawes et al, 2000; LaVail et al, 1987a; Fogerty and Besharse, 2014)) and in BALB/c mice (Santos et al, 2010). In our experience infoldings are quite difficult to find and capture by histology.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In IR mode, retinal lesions were visualized as a result of employing small adjustments to the SLO focus which served to accentuate lesion contrast against the RPE and choroidal background. Retinal lesions were found to be retinal infoldings, invaginations and/or deviations as previously reported by histology in other mouse models of retinal degeneration (Akhmedov et al, 2000; Hawes et al, 2000; LaVail et al, 1987a; Fogerty and Besharse, 2014)) and in BALB/c mice (Santos et al, 2010). In our experience infoldings are quite difficult to find and capture by histology.…”
Section: Discussionsupporting
confidence: 73%
“…As a result of this observation we felt it prudent to screen a random cohort of BALB/cJ animals for any evidence of rd-6 (n = 21) (Hawes et al, 2000), rd-7 (n = 12) (Akhmedov et al, 2000), rd-8 (n = 21) (Mattapallil et al, 2012), MFRP (n = 12) (Fogerty and Besharse, 2014) and RPE65 (n = 15) (Wenzel et al, 2001) mutations. All tests for these mutations were negative.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Furthermore, mfrp mutant mice show the appearance of white retinal flecks in fundus images, which in the case of rdx mice were shown to be due to monocyte-derived subretinal macrophages. 26 In this work, microglia/macrophages were seen subretinally in mfrp −/− zebrafish adults. However, no retinal degeneration or photoreceptor loss was seen in histologic sections of any of the zebrafish mfrp mutants, the oldest examined being 5 months of age.…”
Section: Discussionmentioning
confidence: 50%
“…Although the flecked retinal phenotype and photoreceptor degeneration has been characterized in rd6 and rdx mice, and has provided insight into the macrophage-based nature of the fundus flecks, neither nanophthalmia nor hyperopia were observed in these animals. 14,25,26 It has been speculated that species differences, genetic differences, or perhaps nocturnal lifestyle associated with the mouse eye may underlie the difference in eye size response to Mfrp deficiency. 27 In this work, we disrupted translation of full-length zebrafish Mfrp protein at multiple locations in the coding region and found that these mutant alleles uniformly led to nanophthalmia, hyperopia, and increases in subretinal microglia/macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation